Evaluating the Repellent Efficacy of a Vitex trifolia L. Leaf Powder Botanical Formulation Against Oriental Fruit Flies (Bactrocera dorsalis) - Ainun, Andi Dzul Arsyi; Sjam, Sylvia; Sulaeha, Sulaeha; Fitriyanti, Nur Azizah (HAYATI Journal of Biosciences, 2025)
Fruit flies (Diptera: Tephritidae) are important horticultural crop pests that cause significant losses in both crop quality and quantity. Vitex trifolia L., often considered a weed, contains bioactive compounds with potential as fruit fly repellents. This research aims to evaluate the repellent activity of V. trifolia against oriental fruit flies (Bactrocera dorsalis) at various concentrations. Laboratory experiments were conducted using a completely randomized design (CRD) with four treatments (1%, 3%, 5%) and one control, each repeated five times, Testing was carried out using an olfactometer. The results showed that all tested concentrations significantly reduced B. dorsalis visits compared to the control (0%), with the highest repellency (65.83%) observed at the 5% concentration. A negative linear relationship was established between formulation concentration and B. dorsalis activity, including visits, ovipositor punctures, and larval presence. The formulation significantly decreased oviposition punctures and larval infestation, resulting in a lower percentage of infested fruits (28.57% at 5% concentration compared to 82.86% in the control). Physical and organoleptic assessments confirmed the formulation's suitability for practical application, with a moisture content of (2.66%), a light green color, and a distinctive spicy aroma. Gas Chromatography–Mass Spectrometry (GC-MS) analysis identified key bioactive compounds, including phenol, methyl β-D-glucopyranoside, vitexifolin D, and viteosin A, which are known for their repellent properties. These findings suggest that V. trifolia leaf powder is a promising, eco-friendly alternative for managing B. dorsalis infestations in horticultural crops.